1997
DOI: 10.1002/(sici)1097-0215(19970410)71:2<192::aid-ijc11>3.0.co;2-k
|View full text |Cite
|
Sign up to set email alerts
|

CYP1A1 CYP2E1 and GSTM1 polymorphisms are not associated with susceptibility to squamous-cell carcinoma of the esophagus

Abstract: We investigated the genetic polymorphisms of CYP1A1, CYP2E1 and GSTM1 in Japanese esophageal cancer patients (n 5 53) with a histological diagnosis of squamous-cell carcinoma, to determine whether susceptibility to esophageal cancer is associated with these polymorphisms. There were no significant differences in the frequency distribution of any one of the 3 polymorphisms between esophageal cancer patients and 132 healthy Japanese controls. The genotype distributions in tobacco smokers or alcohol drinkers were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
25
1
1

Year Published

1998
1998
2016
2016

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 62 publications
(29 citation statements)
references
References 20 publications
(15 reference statements)
2
25
1
1
Order By: Relevance
“…In contrast, the CYP1A1 MspI genetic polymorphism was not found to be associated with elevated oesophageal cancer risk. Several studies on ethnic Japanese populations reported no association between CYP1A1 MspI and exon 7 polymorphisms and risk of oesophageal cancer (Hori et al, 1997;Morita et al, 1997;van Lieshout et al, 1999). However, their small case popula- CYP1A1 and oesophageal cancer M-T Wu et al tion (less than 100 oesophageal cancer cases were investigated) may not be sufficient to make a scientific determination regarding genotype significance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, the CYP1A1 MspI genetic polymorphism was not found to be associated with elevated oesophageal cancer risk. Several studies on ethnic Japanese populations reported no association between CYP1A1 MspI and exon 7 polymorphisms and risk of oesophageal cancer (Hori et al, 1997;Morita et al, 1997;van Lieshout et al, 1999). However, their small case popula- CYP1A1 and oesophageal cancer M-T Wu et al tion (less than 100 oesophageal cancer cases were investigated) may not be sufficient to make a scientific determination regarding genotype significance.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have suggested that variant alleles of CYP1A1 MspI polymorphism are associated with malignancies, particularly lung cancer (Kawarjiri et al, 1990;Nakachi et al, 1991;Hayashi et al, 1992;Xu et al, 1996). As reported by Bartsch et al (2000), no association was identified between CYP1A1 MspI and exon 7 polymorphisms and oesophageal cancer risk in a series of studies done on populations of Caucasians and Japanese (Lucas et al, 1996;Hori et al, 1997;Morita et al, 1997;van Lieshout et al, 1999). However, Nimura et al (1997) studied 89 oesophageal carcinoma patients and 137 cancer-free control patients in an ethnically Chinese population and reported that heavy smokers with Val/Val genotypes of CYP1A1 exon 7 had a three-fold risk of developing oesophageal cancer as compared to those with Ile/Ile genotypes.…”
mentioning
confidence: 89%
“…Increased risk of oral (Hung et al, 1997), nasopharyngeal (Hildesheim et al, 1997) and liver (Ladero et al, 1996) cancers were observed in rare genotype or allele carriers in another few studies. However, many other studies did not find any significant association between the CYP2E1 polymorphisms and cancer risks of the oral cavity and pharynx (Matthias et al, 1998), oesophagus (Morita et al, 1997), stomach (Kato et al, 1995;Nishimoto et al, 2000), lung (Kato et al, 1992;Hirvonen et al, 1993;London et al, 1993;Persson et al, 1993), and bladder (Anwar et al, 1996).…”
Section: Discussionmentioning
confidence: 96%
“…Individuals with the CYP2E1*c1*c1 genotype possessed a much greater risk of developing ESCC compared with those carrying the CYP2E1*c2 allele among Chinese drinkers; Furthermore, CYP2E1*c1*c1 exhibits a synergistic interaction with ALDH2*1*2 and methylenetetrahydrofolate reductase (MTHFR)677 (C/T+T/T) (62,63). However, in several cases, particularly in Caucasians, gene polymorphisms of CYP2E1 have no association with esophageal cancer (64)(65)(66)(67).…”
Section: Interactions Between Alcohol Consumption and The Correspondimentioning
confidence: 99%